Spontaneous deleterious mutation in Arabidopsis thaliana - Schultz, Stewart T. (The National Academy of Sciences, 1999)
The frequency and selective impact of deleterious mutations are fundamental parameters in evolutionary theory, yet they have not been directly measured in a plant species. To estimate these quantities, we allowed spontaneous mutations to accumulate for 10 generations in 1,000 inbred lines of the annual, self-fertilizing plant Arabidopsis thaliana and assayed fitness differences between generations 0 and 10 in a common garden. Germination rate, fruit set, and number of seeds per fruit each declined by less than 1% per generation in the mutation lines, and total fitness declined by 0.9% per generation. Among-line variances increased in the mutation lines for all traits. Application of an equal-effects model suggests a downwardly biased genomic deleterious mutation rate of 0.1 and a upwardly biased effect of individual mutations on total fitness of 20%. This genomic deleterious mutation rate is consistent with estimates of nucleotide substitution rates in flowering plants, the genome size of Arabidopsis, and the equilibrium inbreeding depression observed in this highly selfing plant species.